EFFECTS OF ETHANOLIC EXTRACT OF DATURA STRAMONIUM LEAVES ON THE HISTOMORPHOLOGY AND BIOCHEMICAL INDICES OF LIVER AND KIDNEY FUNCTIONS IN RATS - JL HAMIDU; AB ADELAIYE; TW JACKS (Ntec Specialist, 2001)
Background: Changes in histomorphology and some indices of liver and kidney functions were studied in rats administered doses of ethanolic extracts of Datura stramonium leaves. Methods: Four experimental groups of rats were respectively given oral doses of 50mg/kg, 100mg/kg and 200mg/kg of the extract daily for six weeks. Rats were sacrificed at the end of the six weeks and blood samples were collected for biochemical analysis. The livers and kidneys of the rates were harvested for histological studies. Results: The results showed that alanine transaminase (ALT) and bilirubin levels were significantly (P less than 0.05) higher in the groups administered 100mg/kg and 200mg/kg extracts than the control group. The extracts at similar doses also increased significantly (p less than 0.05) the serum urea and creatinine levels. Histological evaluation of the organs of localization revealed dose-dependent effects of treatment with the extract. Conclusion: The study has shown that Datura stramonium leaf extracts administered with 100 200mg/kg for six weeks caused liver and kidney damages in rats